Water scarcity under a changing climate in Ghana: options for livelihoods adaptation - Gyampoh, B.A.; Idinoba, M.; Amisah, S. (Springer, 2008)
The effects of climate change and variability on water availability in Ghana is being felt throughout the country. Coping with water scarcity has become a major issue. Most communities in the Offin River basin are rural with no pipe-borne water, and consist predominantly of farmers who depend on irrigation for their crops. The basin provides the communities with water for drinking, and for other economic activities. Benjamin Apraku Gyampoh, Monica Idinoba and Steve Amisah look at livelihood options to cope with water scarcity as the climate situation worsens in the coming years